THE INFLUENCE OF POSITIONING ON THE QUALITY OF BREAST MAGNETIC RESONANCE IMAGES - Diniz, Camila Leal; Oliveira, Ilse Franco de; Freitas-Junior, Ruffo de; Ruiz, Cristina Pinto Naldi; Almeida, Paulinelly Messias de; Sousa, Rosemar Macedo (Mastology, 2021)
Objective: To evaluate and adapt the positioning pattern of patients to perform breast resonance, allowing for greater comfort and better image quality. Methodology: Prospective study of qualitative evaluation with an experience report carried out with a volunteer without a clinical history of breast disease, in three different brand devices (X, Y, and Z) with coils dedicated to the examination, all of them having four-channel bilateral synergy. Results: In the X equipment test, the coil was coupled to a head coil, with specific support for the head and neck regions, providing greater stability for the area, which caused greater patient comfort. In the three pieces of equipment (X, Y, and Z), the arms were extended forward with specific supports. However, there was a need for greater care with the region, because during the examinations, these supports were not enough and caused discomfort in the shoulder region, which was hampered by the position and overload due to the examination time. In equipment Y, an artifact is formed due to poor positioning and the breasts had to be repositioned, causing an increase in the examination time, which generated greater discomfort. In the three pieces of equipment, in the T2, and diffusion-weighted imaging acquisitions, there was an intense vibration of the table that caused discomfort, as this situation had not been reported before the beginning of the examination. In equipment Z, the coil does not extend along the inclined table, causing greater discomfort in the area of the sacral loin due to tension in the region. Conclusion: After evaluation, it was observed that the positioning interferes in the quality of the images generated and it was decided to build a Decision Matrix for standardization and adequacy.